Profiling Saltwater Recreational Anglers toward the Threats of Marine Environment - CHI, Jennifer; CHI, Yeong Nain (International Journal of Management and Sustainability, 2018)
This study utilized cross-sectional data extracted from the 2013 National Saltwater Angler Survey, conducted by NOAA Fisheries Service, to examine saltwater recreational anglers’ concerns to the threats of marine environment, identify groups exhibiting common patterns of responses, and examine the association between clusters of identified socio-demographic characteristics. The format of marine environmental threats in this study was composed of 13 Likert-scaled items scored from severe threat to not a threat at all. Concerns of marine environmental threats from these participants were examined through factor analysis which identified three reliable factors. Cluster analysis was used to identify three prominent clusters. Statistical tests were used to investigate the association between socio-demographic characteristics, including age, gender, income level, educational level, region of the respondent, and the identified factors and clusters. Results of this study may provide insight to understanding saltwater recreational anglers’ concerns of marine environmental threats and could be an indicator of potential participation and behavior of saltwater recreational fishing projects.